Modulation of 8-Oxoguanine DNA glycosylase 1 (OGG1) alleviated anaemia severity and excessive cytokines release during Plasmodium berghei malaria in mice - Basir, Rusliza; Abas @ Buang, Razif; Hussain, Mohd Khairi; Nordin, Norshariza; Abdullah, Maizaton Atmadini; Abd Aziz, Nur Aimi Liyana; Abdullahi, Samaila; Gambo, Mukhtar Lawal; Abd Majid, Roslaini (Tehran University of Medical Sciences,Danishgah-i Ulum-i Pizishki-i Tihran, 2024)
Background: The interplay of OGG1, 8-Oxoguanine, and oxidative stress triggers the exaggerated release of cytokines during malaria, which worsens the outcome of the disease. We aimed to investigate the involvement of OGG1 in malaria and assess the effect of modulating its activity on the cytokine environment and anemia during P. berghei malaria in mice. Methods: Plasmodium berghei ANKA infection in ICR mice was used as a malaria model. OGG1 concentration and oxidative stress levels in P. berghei-infected mice and their control counterparts were assessed during malaria using enzyme-linked immunosorbent assay. OGG1 activity in malaria mice was modulated using treatment with TH5487 and O8-OGG1 inhibitors. The effects of modulating OGG1 activity using OGG1 inhibitors on cytokine release and anemia during P. berghei malaria infection were assessed by cytometric bead array and measurement of total normal red blood cell count respectively. Results: The plasma OGG1 level was significantly upregulated and positively correlated with parasitemia during P. berghei malaria in mice. Modulation of OGG1 ameliorated malaria severity by improving the total normal RBC count in TH5487 and O8-treated mice. Modulation of OGG1 with TH5487 caused significant reductions in serum levels of TNF-α, IFN-γ, IL-6, and IL-10. Similarly, OGG1 modulation activity using an O8-OGG1 inhibitor caused a significant reduction in serum levels of TNF-α, IL-2, IL-6, and IL-10. Conclusion: The findings indicate the involvement of OGG1 in the P. berghei malaria infection. OGG1 inhibition by TH5487 and O8-OGG1 inhibitors suppressed excessive cytokine release, and this may represent a novel therapeutic strategy for ameliorating the severity of malaria infection.